The Principal’s Oversight of the Project’s Execution to improve the Pancasila Student Profile - Feri, Feri; Kristiawan, Muhammad; Furkan, Nuril (PPSDP International Journal of Education, 2025)
This research aims to describe and analyze the principal’s oversight of the project’s execution to improve the Pancasila student profile, as well as to describe and analyze the challenges faced and solutions employed in the program’s implementation. This study employs a qualitative with data obtained through direct interviews, observations, and documentation. The findings conclude the principals have carried out management functions 1) planning function through participatory planning involving other parties to support this project; 2) organizing the potential of educational resources available in the school; 3) conducting this project (P5) activities in line with the implementation flow of the Pancasila Student Profile strengthening project; 4) Providing direct and indirect guidance, coaching, and mentoring in P5 activities. Challenges faced by school principals 1) human resource factors; 2) content-related factors of P5 activities; 3) value dimensions to be achieved in P5 activities; 4) implementation arrangement factors for P5 activities; 5) local wisdom factors. Solutions undertaken include; 1) conducting pre-P5 activities; 2) coordinating with school committees to encourage parents to motivate their children to actively participate in P5 activities; 3) reflecting on P5 activities; 4) re-internalizing and revitalizing the concept of P5 implementation; 5) conducting P5 activities based on local wisdom in accordance with the P5 activity flow; 6) determining the value dimensions, themes, and time allocation adjusted to co-curricular and extracurricular activities.